Taxation, Corruption and the Exchange Rate Regime - Carsten Hefeker (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
The paper analyzes the relation between institutional quality, such as corruption, in a country and its monetary regime. It is shown that a credibly fixed exchange rate to a low inflation country, like a currency board, can reduce corruption and improve the fiscal system. A monetary union, however, has ambiguous effects. I find that that there is convergence between countries with regard to the level of corruption.
Keywords: D72; E63; F33; 330; Exchange Rate Regime; Monetary Policy; Fiscal Policy; Seigniorage; Corruption; Developing and Transition Countries